On Categories and the Countability of Things Bureaucratic: Turning From Wilson (Back) to Interpretation. Issue 3 (14th December 2019) - Carpenter, Daniel
Abstract: The formulation and application of categories was the handiwork of frontier scholars of public management and remains the essential task of scholars of bureaucracy and regulation. These scholars, exemplified by James Q. Wilson, pioneered the development of categories in three domains: (1) the inductive assignment of observed objects to conceptual groups (a form of Weberian categorization), (2) the deductive assignment of incentives and styles to conceptual groups (type-dependent theorization), and (3) the empirical assignment of observed objects to applied analytic categories (behavioralist measurement). I find in Varieties of Police Behavior (1968) the origins of his enduring categories in Bureaucracy (1988). His classification of agency personnel into executives, managers, and operators remains perhaps his crowning achievement in administrative research. Yet Wilson examined these categories with greater care than is often demonstrated by his successors, as he was careful to condition his comparisons across and within categories. The extension of truly "Wilsonian" principles of analysis to bureaucratic organization requires not simply the development of conceptual structures and the careful consideration of bureaucratic incentives, but also a reappreciation of administrative routines, practices, concepts, and technologies. It may compel the admission that some quantitative and qualitative comparisons are literally, even mathematically, nonsensical.